Case presentation and panel discussion: Transitions in care. (5th December 2022) - Katz, Jennifer; Mercer, David F.; Schuetz, Philipp; Mundi, Manpreet S.; Pimiento, Jose; Morrison, Chet; Mechanick, Jeffrey I.; Patel, Jayshil J.
Abstract: There is evidence that significant quality problems arise as patients transitions in care from one setting to another. Attention to nutrition during transitions of care is important to avoid complication. During the American Society for Parenteral and Enteral Nutrition 2022 preconference course, nutrition during transition of care from pediatric to adult care, from the intensive care unit to the hospital floors and from the hospital to home was addressed.